Draft Genome Sequence of a Copper-Resistant Marine Bacterium, Pantoea Agglomerans Strain Lmae-2, a Bacterial Strain with Potential Use in Bioremediation - Castillo-Nara, A; Tello-Reyes, M; Valdes-Parra, N; Cottet-Bustamante, L (American Society for Microbiology, 2016)
Pantoea agglomerans LMAE-2 was isolated from seabed sediment moderately contaminated with Cu2+. Here, we report its draft genome sequence, which has a size of 4.98 Mb. The presence of cop genes related with copper homeostasis in its genome may explain the resistance and strengthen its potential for use as bioremediation agent. © 2016 Corsini et al.